2020
DOI: 10.3892/etm.2020.9336
|View full text |Cite
|
Sign up to set email alerts
|

Importance of food in the control of inflammation in atopic dermatitis

Abstract: Patients that suffer from inflammatory diseases need to pay special attention to nutrition. For this reason, it is very important to change the approach of both health professionals and food industry specialists. There must be a close collaboration, starting from research, the development phase of foods for special nutrition states. Our primary objective was to identify foods or potential dietary ingredients, which efficacy in the treatment of atopic dermatitis had been scientifically demonstrated in vitro, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Functional foods and dietary supplements can be considered nutraceuticals. Considering the general principles of food development for special nutritional states, presented by Rotaru M et al [18], we believe that they can be an important tool in the development of nutraceuticals. Based on the etiopathogenesis of acne, the researchers Kurokawa and Nakase [10] believe that antioxidants, vitamin D analogues [5,27] and antimicrobial peptides are potential treatments for acne in the future, along with topical anti-androgens, melanocortin receptor antagonists, IGF-1 inhibitors, PPAR modulators, acetylcholine inhibitors, local retinoic and metabolic blocking agents, monoclonal antibodies, phosphodiesterase inhibitors, IL-1β inhibitors, dapson, systemic antiandrogens and immunotherapy.…”
Section: Active Substancementioning
confidence: 89%
See 2 more Smart Citations
“…Functional foods and dietary supplements can be considered nutraceuticals. Considering the general principles of food development for special nutritional states, presented by Rotaru M et al [18], we believe that they can be an important tool in the development of nutraceuticals. Based on the etiopathogenesis of acne, the researchers Kurokawa and Nakase [10] believe that antioxidants, vitamin D analogues [5,27] and antimicrobial peptides are potential treatments for acne in the future, along with topical anti-androgens, melanocortin receptor antagonists, IGF-1 inhibitors, PPAR modulators, acetylcholine inhibitors, local retinoic and metabolic blocking agents, monoclonal antibodies, phosphodiesterase inhibitors, IL-1β inhibitors, dapson, systemic antiandrogens and immunotherapy.…”
Section: Active Substancementioning
confidence: 89%
“…The main action monitored and demonstrated Duolac ® ATP *, 2 × 106 CFU/200 μL/day [18] -Treg differentiation: CD4 + T ↑ proliferation, Foxp3 +/Tregs ↑, IL -10 ↑; -IFN-γ ↑, IL-4 ↓ [18] Strawberry seed extract (tilirosida), 1.0 -3.0 μg/mL [18] -Synthesis of ceramides in the stratum corneum ↑, with the exception of ceramide [EOS], [AP]; -Skin barrier function and moisture retention ↑; -GCS and GBA ↑; -SPT2 and CerS3unaffected [18] L. sakei WIKIM30, 2 × 109 CFU, oral [18] -DC and T cell modulation: In the case of golden hamsters, the treatment with orange essential oil could significantly decrease the growth rate of the sebaceous gland compared to the corresponding dose of juice groups (p < 0.05). Both groups of patients treated with essential oil or bergamot juice and those treated with orange or sweet orange essential oil reported the effect of lowering the growth rate of sebaceous glands with a dose-effect relationship [19].…”
Section: Active Substancementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is toxicity and side effects associateed ewith long-term use of antihistamines, immunosuppressants and local corticosteroids. Therefore, there is a need for new insight and therapeutic materials in the treatment of AD; natural products [25], and herbal medicines [26] have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…A database research identified more AD in children with positive immunoglobulin (Ig)E for fruits than negative specific IgE [ 9 ]. The role of egg white and its components in AD implied the importance of food in the control of inflammation [ 10 , 11 ]. The inflammatory condition of Kawasaki disease has also been associated with AD [ 12 ].…”
Section: Introductionmentioning
confidence: 99%